Secretion of related factors and AMPK/PGC-1 α signal pathway by alveolar macrophages in viral acute lung injury: Secretion in viral acute lung injury - Fan, Zhengfei; Zhu, Jiawei (Cellular and Molecular Biology, 2023)
This study was to investigate the secretion of related factors by alveolar macrophages and AMPK/PGC-1 α signal pathway in viral acute lung injury (VALI) patients. 30 SD rats were randomly divided into blank control group (BCG) and VALI group (VALIG) with 15 rats in each group. The model of VALIG was induced by polyI: C and the BCG was given the same amount of normal saline. The IL-6, IL-8 and TNF-α levels in bronchoalveolar lavage fluid (BALF) were detected by ELISA. The protein, surface markers of alveolar macrophages, and related mRNA expression were detected by Western blot, ELISA, and qRT-PCR. IL-8, IL-6, TNF-α, MUC5AC and TLR4 levels in VALIG were raised than those in BCG (P<0.05), while the AQP5 level was reduced than that in the BCG (P<0.05). The Bcl-2 protein level in the VALIG was reduced than that in the BCG (P<0.05), while the Caspase3 protein level was raised than that in the BCG (P<0.05). The AMPK and PGC-1 α mRNA and protein expression level in the VALIG rat lung tissue was lower than that of the BCG (P<0.05) VALIG is related to inflammatory damage, activation of alveolar macrophages, and secretion of related factors by alveolar macrophages. This may be related to AMPK/PGC-1 α signal pathways.